2021
DOI: 10.1111/jen.12965
|View full text |Cite
|
Sign up to set email alerts
|

Ground cover vegetation promotes biological control and yield in pear orchards

Abstract: The use of ground cover vegetation is becoming a prominent way of promoting biodiversity and associated ecosystem services in Chinese orchards. Despite the large number of studies that have addressed the effects of ground cover vegetation on promoting natural enemy populations and related pest control, it is still unclear whether enhanced natural pest control can increase yield and reduce the use of pesticide. We performed an experiment comparing three cover vegetation practices (ryegrass, clover and hairy vet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Similarly, meta‐analysis studies have indicated that the abundance of plant species promotes pest regulatory services by enhancing predator and parasitoid abundance, predation, and parasitism (Wan et al, 2021). Field studies in orchard management revealed that organic GC boosted fruit yield by 10% while decreasing pesticide use by 51% (Ji et al, 2022). In addition, using border crops in urban agriculture has shown that insecticide use reduced while crop yields increased (Wan, Cai, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, meta‐analysis studies have indicated that the abundance of plant species promotes pest regulatory services by enhancing predator and parasitoid abundance, predation, and parasitism (Wan et al, 2021). Field studies in orchard management revealed that organic GC boosted fruit yield by 10% while decreasing pesticide use by 51% (Ji et al, 2022). In addition, using border crops in urban agriculture has shown that insecticide use reduced while crop yields increased (Wan, Cai, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it can be stated that the maintenance of spontaneous vegetation in orchards favors the permanence of predators, acting as a refuge and reservoir for these natural enemies (Altieri 1999, Prischmann & James 2003. Certain plants associated with orchards play an important ecological role as they are hosts of species that help in the biological control of agricultural pests, as they naturally migrate from this spontaneous vegetation to the main crop of the orchard (Tixier et al 2000, Lykouressis et al 2008, Ji et al 2022). These plants can provide shelter and food, such as pollen, for predatory mites, keeping them in these areas even in periods with unfavorable abiotic conditions or when there is a shortage of prey (Landis et al 2000, Tixier et al 2000, Demite & Feres 2005, assisting in the colonization of these areas through aerial dispersal (Tixier et al 2000, Jung & Croft 2001.…”
Section: Discussionmentioning
confidence: 99%
“…The morphology of some of these plants consists of trichomes, domatia and nectaries, which are beneficial structures for the plant and offer refuge, a safe place for oviposition and provide alternative foods such as pollen and nectar to mite species (Agrawal & Karban 1997, Ferla & Moraes 2002, Prischmann & James 2003, Matos et al 2006, Duso et al 2010. Certain plants, associated with orchards, play an important ecological role as they host species that help in the biological control of agricultural pests, as they naturally migrate from this spontaneous vegetation to the main crop of the orchard (Tixier et al 2000, Altieri 2002, Kreiter et al 2003, Lykouressis et al 2008, Ji et al 2022.…”
Section: Introductionmentioning
confidence: 99%
“…Attributes of vegetation physical architecture, above and below ground, also provide alternative food and shelter for arthropods and mesofauna [21][22][23]. More specifically, ground cover vegetation in perennial systems is seen to increase the abundance of natural enemies [24] as well as influence herbivorous pest species, natural enemies and their interactions in vineyards, depending also on the landscape context [25,26]. Flower-rich cover-crop mixtures in vineyards are expected to increase the abundance of a range of natural enemies, including carabids [27][28][29].…”
Section: Introductionmentioning
confidence: 99%